Faktor-Faktor Yang Mempengaruhi Terjadinya diabetes Melitus di Puskesmas Harapan Raya Tahun 2018 - Imelda, Sonta Imelda (Universitasdiwangsa Jambi, 2019)
Diabetes mellitus (DM) is a chronic multi-system disease associated with abnormal insulin production, inability to use insulin or both. The mortality rate due to DM disease worldwide reaches 1.5 million people in 2014. The prevalence of DM patients is estimated to reach 9% of the total world population. The prevalence of DM patients in Indonesia ranks 4th in the world with 12 million sufferers and is expected to increase to 21.3 million in 2030. The type of quantitative research with the design is descriptive, the research period is 11-13 February 2018. The population is 167 people, the sample is 118 people and the sampling technique is accidental sampling. The analysis technique performed is Univariate. The results of the study found that, of the 118 respondents who suffered from Diabetes Mellitus which affected the majority of 50-59 years old 70 respondents (59.4%), the majority of women were 72 respondents (61%), descendants who had a history of DM 80 respondents (68 %), Food Pattern Factors the majority are unhealthy 69 respondents (59%) and the majority of Physical Activity Factors are not often 88 respondents (74.6%). The conclusions from this study are the factors that most influence the occurrence of diabetes mellitus, namely factors of lack of activity and also the history of heredity and unhealthy eating patterns. Suggestions should the Puskesmas party improve diabetes mellitus counseling.   Keywords: Diabetes Mellitus, Factors affecting DM References: 41 References (2005-2016)